2016
DOI: 10.1016/j.toxlet.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin B increases intrinsic muscle activity in organotypic spinal cord–skeletal muscle co-cultures

Abstract: In organotypic spinal cord-skeletal muscle co-cultures, motoneurons are driven by locomotor commands and induce contractions in surrounding muscle fibres. Using these co-cultures, it has been shown that effects of organophosphorus compounds on neuromuscular synapses can be determined in vitro. In the present study we aimed to extend this in vitro tool for pharmacologic testing of botulinum toxin B. This neurotoxin is widely used for the treatment of dystonia. Besides its effects on the neuromuscular junction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, no ICC was detected, and peristalsis was even enhanced by neurotoxin in ex vivo guts, indicating that peristalsis in ex vivo gut is not due to ICC functionality. Likewise, botulinum toxin could even increase muscular activity in a spinal cord–muscle coculture system [ 44 ]. In short, our cultured ex vivo gut has mesenchymal layers which can be useful for studying epithelial motility.…”
Section: Discussionmentioning
confidence: 99%
“…However, no ICC was detected, and peristalsis was even enhanced by neurotoxin in ex vivo guts, indicating that peristalsis in ex vivo gut is not due to ICC functionality. Likewise, botulinum toxin could even increase muscular activity in a spinal cord–muscle coculture system [ 44 ]. In short, our cultured ex vivo gut has mesenchymal layers which can be useful for studying epithelial motility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been considerable interest in developing neuromuscular junction models in vitro . Several models have relied on open architecture, common-culture of MNs and skeletal myocytes ( Das et al, 2007 ; Drexler et al, 2011 ; Eckle et al, 2016 ), while more recent studies have demonstrated the feasibility of compartmentalized MN/myotube co-cultures ( Zahavi et al, 2015 ; Uzel et al, 2016 ). These preparations exhibit immunohistochemical markers as well as electrophysiological and/or contractile events characteristic of functional neuromuscular transmission.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a homologous mouse-mouse model, which uses explants of embryonic mouse spinal cord and skeletal muscle, contractions of skeletal muscle cells are completely suppressed by succinylcholine (aka suxamethonium) [ 99 , 100 ], a depolarizing nAChR agonist and an NMJ blocker. Contractions in this model are also suppressed by nAChR antagonist rocuronium [ 119 ], as well as by AChE inhibitors, such as soman and VX [ 100 , 120 ], and by botulinum toxin [ 98 ], which blocks release of ACh from presynaptic terminals. Furthermore, in a homologous rat-rat model, in which both spinal cord and skeletal muscle cells are obtained from rat embryos, the pattern of contractions is modulated by application of strychnine and bicuculline, which antagonize effects of inhibitory neurotransmitters glycine and GABA, respectively, as well as by electrical stimulation of spinal cord explants [ 68 ], which underscores the role of motor neurons in driving the muscle activity.…”
Section: The Experimental Model Of the In Vitro Innervated Human Smentioning
confidence: 99%